Correlation between hedonic liking and facial expression measurement using dynamic affective response representation. (June 2018) - Zhi, Ruicong; Wan, Jingwei; Zhang, Dezheng; Li, Weiping
Abstract: Emotional reactions towards products play an essential role in consumers' decision making, and are more important than rational evaluation of sensory attributes. It is crucial to understand consumers' emotion, and the relationship between sensory properties, human liking and choice. There are many inconsistencies between Asian and Western consumers in the usage of hedonic scale, as well as the intensity of facial reactions, due to different culture and consuming habits. However, very few studies discussed the facial responses characteristics of Asian consumers during food consumption. In this paper, explicit liking measurement (hedonic scale) and implicit emotional measurement (facial expressions) were evaluated to judge the consumers' emotions elicited by five types of juices. The contributions of this study included: (1) Constructed the relationship model between hedonic liking and facial expressions analyzed by face reading technology. Negative emotions "sadness", "anger", and "disgust" showed noticeable high negative correlation tendency to hedonic scores. The "liking" hedonic scores could be characterized by positive emotion "happiness". (2) Several emotional intensity based parameters, especially dynamic parameter, were extracted to describe the facial characteristic in sensory evaluation procedure. Both amplitude information and frequency information were involved in the dynamic parameters to remain more information of the emotional responses signals. From the comparison of four types of emotional descriptive parameters, the maximum parameter and dynamic parameter were suggested to be utilized for representing emotional state and intensities. Graphical abstract: Unlabelled Image Highlights: Construct relationship model between psychological linear scale and emotional state Automatic facial expression analysis technology is utilized for emotion judgement Dynamic information parameters are extracted from emotional response signals Dynamic parameters could better represent emotional state and intensities